2021
DOI: 10.1101/2021.02.28.432952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbial structural variations as determinants of human bile acid metabolism

Abstract: Bile acids (BAs) facilitate intestinal fat absorption and act as important signaling molecules in host-gut microbiota crosstalk. BA-metabolizing pathways in the microbial community have been identified, but how the highly variable genomes of gut bacteria interact with host BA metabolism remains largely unknown. We characterized 8,282 structural variants (SVs) of 55 bacterial species in the gut microbiomes of 1,437 individuals from two Dutch cohorts and performed a systematic association study with 39 plasma BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The diversity and composition of the gut microbiome have been studied for over a decade, but their precise roles in influencing host physiology and maintaining tissue homeostasis are still under intense investigation. [32,33] In this study, we found that ampicillin-induced gut dysbiosis led to unbalanced Firmicutes/Bacteroidetes ratios and reduced production of secondary bile acids. Bile acids are synthesized from cholesterol in the liver and further metabolized by the gut microbiota into secondary bile acids to exert biological functions.…”
Section: Discussionmentioning
confidence: 62%
“…The diversity and composition of the gut microbiome have been studied for over a decade, but their precise roles in influencing host physiology and maintaining tissue homeostasis are still under intense investigation. [32,33] In this study, we found that ampicillin-induced gut dysbiosis led to unbalanced Firmicutes/Bacteroidetes ratios and reduced production of secondary bile acids. Bile acids are synthesized from cholesterol in the liver and further metabolized by the gut microbiota into secondary bile acids to exert biological functions.…”
Section: Discussionmentioning
confidence: 62%
“…Next, we explored associations between the abundance of crAss-like phages and structural variants (SVs) in bacterial genomes (Wang et al, 2021; Zeevi et al, 2019). Based on the collection of samples from the three independent cohorts LLD, 300OB and IBD, we detected 7,999 deletion structural variants (dSVs, genome segments absent in 25% to 75% samples) and 3,559 variable structural variants (vSVs, genome segments absent in < 25% samples).…”
Section: Resultsmentioning
confidence: 99%